FRAME ANALYSIS OF METAPHORIZATION OF NATURE IN ENGLISH - Ahmedjanova Dilrabo Asatullayevna (Galaxy International Interdisciplinary Research Journal, 2023)
The current article aims to explore main concept of the term nature, its use in metaphorical meaning. There are also conducted some investigation about frame analysis about the interpretation on natural phenomenon. The author claimed figurative use of metaphorization and concept of nature clearly in this article.